Yadnya Adalah Ketulusan, Bukan Kontestasi Yang Dibalut Gengsi Dalam Kehidupan Beragama - Damiyani, Ni Putu (Metta : Jurnal Ilmu Multidisiplin, 2021)
In Hinduism, yadnya is something that is mandatory to do. Because humans were created by Ida Sang Hyang Widhi Wasa on the basis of yadnya. So that humans should maintain and develop themselves with yadnya as their guideline to improve and devote themselves to Ida Sang Hyang Widhi Wasa. Actually yadnya is a sincerity in life, yadnya comes from the Sanskrit word "yaj" which means sacrifice, offering or sincere and sincere surrender. When talking about yadnya. So it will never be separated from the name upakara in the form of burdentenan (when it is viewed from the context of the ritual). On the days of worship, God is imagined to be present to the devotee as a Bhatara-Bhatari who is welcomed and served cordially as if serving an honored guest. But in reality, the implementation in the field is really deviant. In this digital age 4.0, many Hindu people do not understand the meaning of bantam made / presented so that the banten presented deviates from rules and literature. People nowadays make banten only as a place for contestation to show their abilities, not in accordance with the Vedic scriptures. If observed together, many of our brothers and sisters converted because they felt defeated by this indirect contestation and many also because of economic reasons and the weakness of their Sradha and Bhakti. But the reason is only self-defense, in fact, if you understand the yadnya itself, everything will feel light. Yadnya is not really a contest in religious life. Yadnya is not a place to show off luxury or prestige alone. Yadnya is a sincere and sincere sacred offering. Yadnya is carried out with a sense of lascarya, sradha and devotion to Ida Sang Hyang Widhi Wasa.